The Operational Practices of Volunteer Networks for Health Care for Patients with Disabilities at Nong Bua Lamphu Hospital - Lamkham, Danai (Journal of the office of disease prevention and control 9 Nakhon Ratchasima, 2023)
The objectives of this research were to study the operation of volunteer networks providing healthcare for patients with disabilities at Nongbua Lamphu Hospital and to compare operational practices based on gender, work experience, and educational levels. Additionally, the study aimed to present guidelines for the development of volunteer networks. A total of 106 participants were involved in data collection. The results are as follows: Overall, the operation of volunteer networks for caring for patients with disabilities was rated at the highest level. The average score for disease prevention was the highest, followed by cure and rehabilitation, and providing materials to assist patients with disabilities. However, health promotion scored at the lowest level. When comparing gender and work experience, differences were found in the operation of health promotion. Furthermore, disease prevention, rehabilitation, and material provision differed among volunteers with varying work experiences. When categorized by education levels, a significant difference was observed in the operation of health promotion (p-value < 0.05). Guidelines for the potential development of volunteer networks for caring for patients with disabilities include the performance of appropriate exercises and the application of local wisdom in health support. Knowledge for family members, support for training, development of occupation, and management of the environment within families should be prioritized. Continuous training may enhance understanding of responsibilities and develop psychological readiness for interacting with patients. Finally, regular monitoring is recommended through monthly meetings.